A Case Report: Myxomatous Mitral Valve Disease in a Shih Tzu - Sheren; Arjentinia , I Putu Yudhi; Widyastuti, Sri Kayati (Universitas Airlangga, 2024)
Myxomatous Mitral Valve Disease (MMVD) is a degenerative condition of the mitral valve where it weakens and causes regurgitation, eventually leading to cardiac remodeling. Jason, a seven-year-old male Shih Tzu weighing 7.5 kg, was presented with a persistent cough and exercise intolerance lasting over a month. A physical examination revealed a Grade II/VI heart murmur. Radiography and echocardiography were performed as part of the laboratory examinations. Radiography demonstrated cardiac remodeling, with a VHS of 10.3 viscerocranial, an intercostal space of 3, and a VLAS of 2.3. Echocardiography unveiled left atrial enlargement, mitral valve regurgitation, and a reduction in heart function. The dog was treated with Pimobendan (Cardisure® 10mg, Dechra, England) as an inodilatator at 0.25mg, Enalapril Maleate 0.5mg/kg (Tenace® 5mg, Combiphar, Indonesia), and furosemide (Farsix® 40mg, Fahrenheit, Indonesia) at 2 mg/kg via oral route twice a day over the course of seven days. Thereafter, the dose was reduced to 1.5 mg/kg PO twice a day for seven days, and eventually once a day for the remainder of the seven days. Following the three-week treatment, there was a significant reduction in the frequency and intensity of coughing.